Role of rock phosphate in alleviation of heavy metals stress on Fusarium oxysporum - H.A.H. Hasan (Plant, Soil and Environment, 2007)
An endophytic fungus of soyabean (Glycine max) roots, Fusarium oxysporum, was used to study its activity under heavy metals (Cd2+, Mn2+ and Zn2+) stress and the role of rock phosphate (RP) in alleviation of the stress. F. oxysporum growth, amino acids and protein were increased by increasing RP concentration (1-6 g/l) after 8 and 14 days. Heavy metals (HM) have a stressing effect on F. oxysporum - a significant decrease of amino acids, protein and accumulation of sugar at 1mM/l follows a descending order of Cd2+ > Mn2+ > Zn2+. RP is altering the stressing effects of metal on F. oxysporum by a significant growth improvement at 3 and 6 g/l RP, increase of amino acids, protein and decrease of sugar. The solubilization of RP increased under HM application, which may be attributed to an increase of the adsorption of HM by increasing RP concentration. RP has the highest adsorption affinity for Cd2+ (81%) followed by Zn2+ (71%) and Mn2+(55%).